Performance Analysis of Screw Turbine Design with Additional Flaps Modification Using Computational Fluid Dynamics Method - Juniarko Prananda; Eddy Setyo Koenhardono; Noerendik Fuathur Farhan (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2021)
Renewable energy is a type of alternative energy that can be utilized to generate electricity. Wind energy is one of the renewable energy sources. Because of Indonesia's equatorial location, the wind characteristics are moderate, with wind direction and speed changing frequently. To harvest wind energy, it is therefore vital to diversify the types of wind turbines. A screw turbine, also known as an Archimedes screw turbine or a screw turbine, is a type of wind turbine that is often employed in micro hydropower plants. The great efficiency of this turbine is a benefit. This screw turbine will use a Horizontal Axis Wind Turbine (HAWT). The advantage of using the horizontal axis over the vertical axis is that the rotor's efficiency is higher. The screw turbine was changed in this study by adding flaps to boost torque and rpm performance while also increasing wind catchment. The model design with the inclusion of 3 cm flaps with a flap angle of 30° has a high torque and angular velocity with a torque value of 0.00609 Nm and an angular velocity of 12.55 rad/s at an airflow velocity of 3.4 m/s, according to the results obtained from model simulation using CFD (119,84 RPM). Power Coefficient (CP) = 0.00659, Torque Coefficient (CQ) = 0.01990, and Tip Speed Ratio (TSR) = 0.331357.